AGROENERGIA, PRODUÇÃO DE ALIMENTOS E DESENVOLVIMENTO SUSTENTÁVEL - Tavares, Jairo J.; Lemes, Fabio R. M.; Bolter, Jairo A. G.; Tavares, Vanessa; Boff, Vilmar A.; Pillon, Pedro P. S. (Salão do Conhecimento, 2013)
Resumo